Development of Student Attendance Application with QR Code Scan - Marwan Hakim; Fitriani Fitriani; Hannatul Ma’we (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
The development of a QR Code-based student attendance application at MA NW Teko effectively addresses the inefficiencies of the previous manual attendance system. The new system improves time efficiency, minimizes fraud, and produces more accurate and accessible attendance records. Built using the CodeIgniter 4 framework with PHP and JavaScript and operated via XAMPP, the application allows real-time management of student attendance data. A key feature is the integration of WhatsApp notifications, which enhances communication between the school and parents. This innovation contributes positively to the digitalization of educational administration processes. While the application is functional and beneficial, further improvements are recommended. Comprehensive testing across various network conditions and user devices is needed to ensure system stability and compatibility. Additionally, scalability and data security must be strengthened, particularly if the system is to be implemented at a broader level. Future versions of the system could also benefit from added features, such as attendance statistics, export options for reporting, and automatic time-based alerts. Lastly, successful adoption of the system will require ongoing training and socialization for teachers and administrative staff to ensure optimal usage and minimize technical obstacles in the field. This application demonstrates how digital tools can enhance administrative efficiency in schools and lays the groundwork for further innovation in education management systems.